Genomes and Transcriptomes of Duckweeds - An, Dong; Li, Changsheng; Zhou, Yong; Wu, Yongrui; Wang, Wenqin (Frontiers in Chemistry, 2018)
Duckweeds (Lemnaceae family) are the smallest flowering plants that adapt to the aquatic environment. They are regarded as the promising sustainable feedstock with the characteristics of high starch storage, fast propagation, and global distribution. The duckweed genome size varies 13-fold ranging from 150 Mb in Spirodela polyrhiza to 1,881 Mb in Wolffia arrhiza. With the development of sequencing technology and bioinformatics, five duckweed genomes from Spirodela and Lemna genera are sequenced and assembled. The genome annotations discover that they share similar protein orthologs, whereas the repeat contents could mainly explain the genome size difference. The gene families responsible for cell growth and expansion, lignin biosynthesis, and flowering are greatly contracted. However, the gene family of glutamate synthase has experienced expansion, indicating their significance in ammonia assimilation and nitrogen transport. The transcriptome is comprehensively sequenced for the genera of Spirodela, Landoltia, and Lemna, including various treatments such as abscisic acid, radiation, heavy metal, and starvation. The analysis of the underlying molecular mechanism and the regulatory network would accelerate their applications in the fields of bioenergy and phytoremediation. The comparative genomics has shown that duckweed genomes contain relatively low gene numbers and more contracted gene families, which may be in parallel with their highly reduced morphology with a simple leaf and primary roots. Still, we are waiting for the advancement of the long read sequencing technology to resolve the complex genomes and transcriptomes for unsequenced Wolffiella and Wolffia due to the large genome sizes and the similarity in their polyploidy.